KOMUNIKASI EKSTRA NORMAL DALAM MEMBANGUN PARIWISATA BUDAYA DI ERA NEW NORMAL - I Putu Agus Aryatnaya Giri; I Made Girinata; I Ketut Wiratmaja (UHN IGB Sugriwa Denpasar, 2020)
The outbreak of the corona virus in Indonesia, of course, has had a very significant impact in all sectors of life, one of which is in the field of cultural tourism. The closed in and out access between islands, between continents, and between countries has resulted in